The Effect of Sensory Integration Activities on the Fine Motor Abilities of Early Childhood - Arwinda; Syamsuardi; Tasrif Akib; Intisari; Nur Alim Amri (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
The low level of fine motor skills in early childhood poses a challenge that can hinder children's independence and school readiness. These obstacles are evident in daily activities such as manipulating scissors, stringing beads, and other tasks requiring hand-eye coordination. Based on sensory integration theory, multisensory stimulation can optimize children's overall motor development. This study aims to analyze the effect of sensory integration activities on improving fine motor skills in early childhood. The research employed a pre-experimental design with a one group pretest-posttest approach. The subjects consisted of 20 children aged 4–5 years selected using a total sampling technique. Data were collected using fine motor skills observation sheets, and data analysis was carried out using the Wilcoxon test. The results showed a significant improvement in fine motor skills after the intervention, with the average score increasing from 23.00 in the pretest to 47.80 in the posttest. The Wilcoxon test revealed a significance value of 0.001 ≤ 0.05, indicating the effectiveness of sensory integration activities in enhancing fine motor skills. This study concludes that integrated sensory stimulation has a positive impact on the development of fine motor skills in early childhood, with implications for its implementation as an alternative stimulation program in early childhood education settings.